Smart Traffic Light Berbasis ESP32 dan Internet of Things menggunakan Logika Fuzzy untuk Pengendalian Kepadatan Lalu Lintas - Haikal Septian Hadi Putra; Abdul Azis; Emidiana Emidiana (CV. ALIM'SPUBLISHING, 2026)
Traffic congestion and zebra crossing violations are common problems at road intersections due to fixed-time traffic light systems that are less adaptive to traffic conditions. This research aims to design and implement an ESP32 and Internet of Things (IoT)-based Smart Traffic Light system using the Mamdani Fuzzy Logic method to automatically regulate traffic light duration based on vehicle density. The system utilizes an inframerah sensor to detect vehicle density and an ultrasonic sensor to detect zebra crossing violations. Sensor data are processed by the ESP32 through fuzzification, inference, and defuzzification to determine the appropriate traffic light duration. The system is equipped with traffic light LEDs, a TM1637 countdown timer, a buzzer, and a Telegram Bot for real-time monitoring. Testing results showed that the inframerah sensor successfully detected vehicle density, while the ultrasonic sensor accurately detected objects at distances of 5–25 cm. The fuzzy logic system produced green light durations of 5, 20, and 30 seconds for low, medium, and high traffic densities, respectively. In addition, the Telegram Bot successfully sent real-time notifications of zebra crossing violations. The proposed system operates automatically, adaptively, and effectively to support traffic management and zebra crossing monitoring.